Prognostic Factors for Eclamptics in Intensive Cares of Two University Teaching Hospitals in Cotonou, Benin - ZOUMENOU, EUGÈNE; AHOUNOU, Ernest (My University, 2023)
Introduction: In Benin, the maternal mortality rate remains high and one of the main causes is preeclampsia in its complicated forms, including eclampsia. For this, treatment is most often provided in an intensive care unit by a multidisciplinary team involving obstetricians and intensive care doctors. Objective: To determine the prognostic factors of eclamptics treated in intensive care units in two university teaching hospitals in Cotonou. Patients and Method: The study was transversal descriptive and analytical with prospective collection of data from May 1 to July 31, 2022, in the intensive care units of CHU-MEL and CNHU-HKM in Cotonou. The sampling was non-probability with exhaustive recruitment of all cases of eclampsia managed in hospital intensive care units. Clinical, therapeutic and evolutionary data were studied. Data analysis was done with Epi info 7.2.1.0 software. Results: Fifty-five eclamptics were included. The incidence was 12.39%. The average age of eclamptics was 24.67 ± 1.41 years, with a reference rate of 85.45%. Primigravidae represented 52.73%. A history of eclampsia and/or high blood pressure (14.54%) was associated with mortality. Cesarean section was indicated in 85.45% and general anesthesia, was the technique used in 95.75% of cases. Eclamptic status was found in 36.37% of patients. Other poor prognostic factors were Glasgow score of less than nine (9.09%), shock (7.27%), mechanical ventilation (58.18%) and complications. Mortality was 16.36%. Conclusion: The mortality of eclamptics in the intensive care units of CHU-MEL and CNHU-HKM was high. Poor prognostic factors were a history of preeclampsia or pregnancy-induced hypertension, severity of eclampsia and complications.
Keywords: Preeclampsia; Prognostic Factors; Resuscitation